Influence of Ctenocephalides felis on biochemical indicators of blood serum of infested cats - Havryk, B.; Melnychuk, V. (Scientific Progress & Innovations, 2025)
Fleas represent one of the most important groups of blood-sucking parasitic insects. An important aspect of the medical and veterinary importance of fleas, which has not lost its relevance even today, is their role in maintaining natural foci of zooanthroponotic and zoonotic infections. With constant flea attacks on an animal, clinical signs develop, characterized by itching, anxiety, and dermatopathologies, which are due to certain parasite-host relationships, which are based on the interaction of the pathogenic effect of the parasite and the host's defense mechanism. The aim of the research was to determine changes in the biochemical parameters of blood serum of infested cats at different levels of ctenocephalic invasion intensity. The conducted studies have established that flea parasitism on the body of cats led to a negative impact of ectoparasites on the biochemical parameters of the blood serum of infested cats. With increasing intensity of flea infestation of cats, the severity of changes in the biochemical parameters of their blood serum increased. Thus, at low levels of ctenocephalic invasion intensity (up to 19 specimens/head), a decrease in albumin content by 3.99 % (p<0.05) was detected in the blood serum of infected cats compared to the levels in clinically healthy cats. All other indicators were within physiological fluctuations. At higher rates of intensity of ctenocephalic invasion (from 20 to 42 specimens/head) in the blood serum of infected cats, a decrease in albumin content by 15.39 % (p<0.01), glucose by 35.99 % (p<0.05), an increase in total bilirubin content by 33.54 % (p<0.05), urea by 36.24 % (p<0.05), creatinine by 16.18 % (p<0.05), as well as an increase in the activity of enzymes alanine aminotransferase by 22.42 % (p<0.05), aspartate aminotransferase by 38.56 % (p<0.05), alkaline phosphatase by 2.4 times (p<0.05), α-Amylase by 51.44 % (p<0.05), gamma-glutamyl transpeptidase by 31.22 % (p<0.05) compared to the indicators in clinically healthy cats. The results obtained expand existing data on the impact of fleas on the body of infested cats, and also allow us to take into account indicators of infestation intensity in increasing the effectiveness of treatment measures.